2f-3f+9g+2f-2f+f=

Simple and best practice solution for 2f-3f+9g+2f-2f+f= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2f-3f+9g+2f-2f+f= equation:


Simplifying
2f + -3f + 9g + 2f + -2f + f = 0

Reorder the terms:
2f + -3f + 2f + -2f + f + 9g = 0

Combine like terms: 2f + -3f = -1f
-1f + 2f + -2f + f + 9g = 0

Combine like terms: -1f + 2f = 1f
1f + -2f + f + 9g = 0

Combine like terms: 1f + -2f = -1f
-1f + f + 9g = 0

Combine like terms: -1f + f = 0
0 + 9g = 0
9g = 0

Solving
9g = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '9'.
g = 0

Simplifying
g = 0

See similar equations:

| 5g+(2+4h-2g)-(4g+2h+3)= | | 30700=50e^3t | | Xy+2x+3y=11 | | (2x-3)(2x-3)+5x=(x-3)*(4x+11) | | 2y+2x=100 | | (3+5i)-(5-3i)= | | 9p-4q+11p+7q= | | a+a-3b+2b= | | c+d+2c-2d= | | 4(t-4)+3t=32-t | | y=100-(t^2-6t) | | (2x-3)(2x-3)=(x-3)(4x+11) | | -3(-13x-37)=-9(-46+4x) | | 3x+x+16=50 | | 4y=-5x+-20 | | (7t+5)-(3t-5)= | | 3x+3y+4=x+2y+1 | | 4x-8=-2x-5 | | (x-6)(x+6)=(x-6)(x-6) | | (x-6)(x+6)=(x-6)x(x-6) | | y-5.9=7.22 | | 8x+18=30 | | 2x^4y^2z^2= | | 0=9x+0.25y | | 3Xsquare-13X-10=0 | | 3y^2-11y-30=0 | | 4+25=100 | | 2(3z+3)=(2+1)(3-5) | | 5f+20-6f-30= | | X-3y=36 | | 20=12((5-x)+x+(4-x))+10-((5-x)+x+(6-x))+11-((4-x)+x+(6-x)) | | 20=(12((5-x)+x+(4-x)))+(10-((5-x)+x+(6-x)))+(11-((4-x)+x+(6-x))) |

Equations solver categories